Investigating applications of university productivity measurement models using Australian data. Issue 12 (2nd December 2019) - Moore, Kenneth; Coates, Hamish; Croucher, Gwilym
ABSTRACT: The paper contributes to the growing and often controversial study of higher education productivity measurement. The paper clarifies core productivity ideas, and considers alternative models for productivity assessment. Results from these models are explored using data from Australian higher education. Findings reveal implications for the technique and the practice of higher education productivity measurement. The paper provides evidence that productivity change estimates in higher education are not robust to the choice of estimation method. The research then demonstrates how the practice of higher education productivity measurement may benefit from approaches different to conventional econometric means of estimating frontier efficiency. Focusing on the drivers of productivity change and on the value weighting of data elements in models may provide more nuanced and actionable information for stakeholders and decision-makers. The paper concludes by urging more work to advance this field.